Fucosylated TLR4 mediates communication between mutualist fucotrophic microbiota and mammalian gut mucosa - Nanthakumar, Nanda N.; Meng, Di; Newburg, David S. (Frontiers in Medicine, 2023)
The glycans on the mucosa of sucking mice are predominantly sialylated; upon weaning, fucosylated glycans preponderate. This is a manifestation of mutualism with fucotrophic bacteria. Investigations on the mechanism whereby bacterial colonization induces mammalian gut fucosylation revealed a novel molecular mediator of general gut fucosylation: a specific form of TLR4 that is itself fucosylated, fuc-TLR4. The activity of this fuc-TLR4 is strikingly distinct from TLR4. This fuc-TLR4 transduces communication between a mutualist pair: the prokaryote fucose-utilizing Gram-negative (fucotrophic) bacteria of the microbiota and the eukaryote mammalian intestinal epithelium. The mechanism involves fucose-binding ligands in the lumen of the gut activating mucosal fuc-TLR4, inducing the fuc-TLR4 dependent non-inflammatory (ERK and JNK dependent, NF-B independent) signaling cascade, initiating induction of fucosyltransferase 2 (secretor) gene transcription. In vitro, either defucosylation or TLR4 knockdown abrogates FUT2 induction, indicating a specific requirement for both the intact TLR peptide backbone and the glycan moieties of fuc-TLR4. In vivo, fucose-utilizing bacteria and fucose-binding ligands induce mucosal fucosylation. Thus, fuc-TLR4-mediated interkingdom communication by fucotrophic pioneering bacteria of the microbiota induces a fucosylated niche, the intestinal mucosa, that facilitates the first step in establishment and maintenance of a fucose-dependent microbial community. Activation of this pathway is essential for recovery from chemically-induced mucosal injury in vivo. This fucotroph, through fuc-TLR4 signaling, supports initial colonization of the gut, recovery from dysbiosis, and restoration or preservation of intestinal homeostasis. Thus, fucosyl-TLR4, through its downstream signaling to the nucleus of the intestinal epithelial cell, mediates bacteria-induced gut fucosylation essential for establishing a healthy fucose-dependent mutualism between the mammalian gut and its resident microbes.